Effect of the baseline pulse wave velocity on short term and long term blood pressure control in primary hypertension. (15th October 2020) - Fan, Y.; Gao, W.; Li, J.; Fan, F.; Qin, X.; Liu, L.; Cheng, X.; Xu, X.; Wang, X.; Wang, B.; Huo, Y.
Abstract: Objectives: Arterial stiffness may affect antihypertensive response to antihypertensive treatment. However, sufficient clinical evidence is lacking. This longitudinal study aimed to evaluate the effect of baseline arterial stiffness measured by the brachial-ankle pulse wave velocity (baPWV) on response to short-term and long-term enalapril-based treatment in 3310 hypertensive adults from the China Stroke Primary Prevention Trial (CSPPT). Methods and results: Blood pressure (BP) measured at three months (short-term) in 2780 subjects, and the time-average on-treatment BP in 3310 subjects during a median of 4.5-year follow-ups (long-term) were analyzed in the study. After short-term antihypertensive treatment, every 1 m/s increase in baPWV denoted a 7% and 6% decreased chance of achieving systolic BP (SBP) control (odds ratio (OR), 0.93; 95% CI 0.90, 0.96; P < 0.001) and BP control (OR, 0.94; 95% CI 0.91, 0.97; P < 0.001), respectively, after adjustment for age, gender and other variables. After long-term treatment, every 1 m/s increase in baPWV posed an 7% and 6% greater risk of failing to attain SBP control (OR, 0.93; 95% CI 0.90, 0.95; P < 0.001) and BP control (OR, 0.94; 95% CI, 0.92, 0.96; P < 0.001), respectively, not regarding for DBP control after both short- and long-term treatment. Higher baseline baPWV significantly decreased SBP reduction both after three months and the median 4.5-year treatment, while increased DBP reduction after the median 4.5-year treatment. Conclusions: Elevated baseline baPWV significantly decreased BP response to short-and long-term treatment in adults with primary hypertensive. Arterial stiffness improvement may be an essential target to achieve adequate BP control. Highlights: The baseline baPWV is an independent predictor of adequate SBP and BP control. Higher baseline baPWV predicts less SBP reduction in a dose response manner. There was no significant association between baseline baPWV and DBP control.